Waste management in the fashion and textile industries - Nayak, Rajkishore; Patnail, Asis (Textile Institute book series., 2021)
Waste Management in the Textiles Industry explores and explains the latest technologies and best practices for an integrated approach to the management and treatment of wastes generated in this industry. Provides a strong technological analysis of the manufacturing supply chain, including spinning, fabric production, finishing, garment manufacture, and the packaging of clothing; Explains how textile technology perspectives feed into management decision-making about sustainability; Addresses the industry's impact on air and water quality and landfill waste.